Tantangan dan Strategi Proses Akreditasi Pendidikan: Kualitas dan Relevansi Pendidikan di Era Modern - Irwan, Andreas Setiadi (Jounal Nyanadassana, 2025)
The education accreditation process is a critical step in ensuring the quality and relevance of education in the modern era. In the face of evolving challenges, education must be able to adapt and meet increasingly high standards. The main objective of this research is to find out how the implementation of accreditation has been, both the challenges and strategies, which have an impact on the quality and relevance of education. Through the results of this research, it is hoped that it can provide an overview for stakeholders in education to optimize the accreditation process. This is a conceptual article that focuses on the systematic literature review methodology. This article first refers to a review of previous studies on education accreditation. The population in this study was all articles related to the theme of educational accreditation. The sample analyzed was 30 literatures. The findings are that accreditation is important to ensure the quality and relevance of education in the modern era. Although there are challenges in its implementation, through the implementation of appropriate strategies with proper attention to the main factors that affect the quality of education, educational institutions can continue to improve their quality and relevance.